STRATEGI GURU DALAM MENERAPKAN MODEL PROBLEM BASED LEARNING PADA PELAJARAN IPAS DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS DI KELAS IV SD IT CAHAYA HATI JAMBI - Sapitri, Bela; Sofwan, Muhammad; Risdalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher's strategies in implementing the Problem Based Learning (PBL) model in IPAS (Natural and Social Science) learning to enhance students' science process skills in Grade IV of SD IT Cahaya Hati Jambi. This study used a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observation, and documentation analysis. The subjects of this study were one IPAS teacher and several Grade IV students. The results showed that: (1) the teacher planned problem-based learning systematically by integrating PBL syntax into the teaching module; (2) the implementation of PBL was carried out according to PBL stages, with the teacher serving as a facilitator and students actively engaged in observation, discussion, problem-solving, and presentation activities; (3) the teacher's strategies to improve science process skills were implemented through authentic problem provision, prompting questions, group work, and process assessment; and (4) the application of PBL had a positive impact on improving students' science process skills, critical thinking, collaboration, communication, and self-confidence. The findings confirm that PBL implementation in IPAS learning is effective in creating more active, meaningful, and contextual learning experiences for elementary school students.